Multiple Relapses of Visceral Leishmaniasis in HIV Co-Infected Patients: A Case Series from Ethiopia - Rezika Mohammed; Helina Fikre; Angela Schuster; Tigist Mekonnen; Johan van Griensven; Ermias Diro (Current Therapeutic Research, 2020)
Background: Human visceral leishmaniasis (VL) is a life-threatening protozoan disease caused by parasites belonging to the Leishmania donovani complex. Ethiopia has the highest VL-HIV co-infection rate in the world, with several of these patients presenting with repeated episodes of VL disease (ie, relapse). However, we lack data on how HIV patients with multiple VL relapse present clinically, and whether they continue to respond to currently available medicines. Methods: The medical records of VL-HIV co-infected patients with multiple VL relapses at the Leishmaniasis Treatment and Research Center in Gondar, Ethiopia, between June 2012 and June 2016 were retrieved. Variables on their clinical and laboratory profiles were collected. Descriptive analysis was done to show the characteristics of the VL episodes. Result: A total of 48 VL episodes in 12 patients were identified, the median number of episodes per patient was 5 (interquartile range, 4–8 episodes). The median time to relapse was 5 months (interquartile range, 3–5.5 months). Splenomegaly was present in 47 of the episodes (98%), fever or other accompanying symptoms were present in only 66% (32 out of 48). The median tissue parasite grade at VL diagnosis was 6+ (interquartile range, 5+– 6+). All patients were on antiretroviral therapy. The median duration of treatment per episode was 2 months (interquartile range, 2–2 months). All patients achieved parasitological cure at discharge at each episode. Conclusions: Multiple recurrences of VL diseases were observed in HIV co-infected patients. With recurrent episodes, splenomegaly was found to be the main manifestation, whereas fever was less common. These patients came with recurrence of diseases in <6 months and required prolonged treatment to achieve cure.Further research on prediction, prevention, and better management options for recurrent VL is needed. ORCID ID: https://orcid.org/0000-0002-1410-0454. (Curr Ther Res Clin Exp. 2020; 81:XXX–XXX)